Yahoo Web Search

  1. ...3 terms to evaluate: (3-6)x + (4-6)x + (5-6)x = 72. Simply the LHS . What does it give? [ = -6x ] Then, solving for x ...

    2 Answers · Science & Mathematics · 11/11/2020

  2. Yep, ordinary algebra.  Divide both sides by the same value and the equation remains balanced.  The LHS still = the RHS.  So divide away and enjoy.

    3 Answers · Science & Mathematics · 19/08/2020

  3. RHS = cot²(x)[csc³(x) - csc(x)] = cot²(x)csc(x)[csc²(x) - 1] = cot²(x)csc(x)cot²(x) = cot⁴(x)csc(x) = LHS

    1 Answers · Science & Mathematics · 09/05/2020

  4. x^2 = y  ...  y is a variable, not a constant like 4 ...  different rules apply   a^y = b^x     a = b^(x/y)  until you know a number value for b and y (which has become a root) we don 't know if the answer is pos, neg, or imaginary.

    2 Answers · Education & Reference · 30/03/2020

  5. ... + Fr = mh''.  Use the correct signs for the LHS terms. Fg is a constant [which one?]. Note that h'...

    1 Answers · Science & Mathematics · 28/02/2020

  6. LHS = xy + xy' = x(y + y') ..........distributive law = x(1) = x RHS = (x+y)(x+y' ) = x+(yy') ...........distributive law = x+(0) .............complement law = x LHS = RHS

    1 Answers · Science & Mathematics · 03/08/2019

  7. ...x = c/d Then x = (c/d) - (a/b) RHS is clearly rational while LHS is irrational. This is a contradiction. Hence the sum must...

    4 Answers · Science & Mathematics · 03/08/2019

  8. ... / R GmM / R = 2*KE and you should recognize the LHS as being equal to -GPE. If you find this helpful, please award...

    1 Answers · Science & Mathematics · 07/05/2019

  9. ... the given P(t) and showing that it equals the LHS . Or you can find the solution by solving the DE this way: ...

    1 Answers · Science & Mathematics · 14/02/2019

  10. ....N. (oxidation number) of H on the LHS = O.N. of H on the RHS = +1...⁻ O.N. of H on the LHS = O.N. of H on the RHS, as...

    3 Answers · Science & Mathematics · 16/02/2019

  1. Try asking your question on Yahoo Answers